Government Size and Economic Growth in Africa and the Organization for Economic Cooperation and Development Countries - Lazarus, Wanjuu Zungwe; Khobai, Hlalefang; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2017)
This study investigates the impact of government expenditure on economic growth of 27 countries of the Organization for Economic Cooperation and Development (OECD), 50 African countries, and 77 OECD and African countries. The study establishes that the optimum government sizes were 36.61%, 15.61%, and 23.13% for the 27 OECD, 50 African, and 77 African and OECD countries, respectively. The actual government sizes were 18.9%, 14.06%, and 18.76% of the RDGP for the 27 OECD countries, 50 African countries, and the 77 OECD and African countries, respectively. The study concludes that there exists inverted u-shape curve in the three panel regression models estimated. The optimum government sizes were below the actual government sizes in the three regression models studied. The optimum government size in Africa countries is lower than the optimum government size in the OECD countries. The low level of government size in Africa countries reflects the low level of economic development in Africa and vice versa for the OECD countries. Keywords: Generalized Method of Moments, Optimum Government Size, Economic Growth JEL Classifications: C23, E62, F43, O47